Radiation Dose During Relativistic Electron Precipitation Events at the International Space Station - H. Ueno; S. Nakahira; R. Kataoka; Y. Asaoka; S. Torii; S. Ozawa; H. Matsumoto; A. Bruno; G.A. deNolfo; G. Collazuol; S.B. Ricciarini (Space Weather)
Abstract We provide a quantitative estimate of the radiation dose during relativistic electron precipitation (REP) events at the International Space Station (ISS). To this goal, we take advantage of the data collected by the CALorimetric Electron Telescope, the Monitor of All‐sky X‐ray Image, and the Space Environment Data Acquisition equipment‐Attached Payload. The three ISS detectors offer complementary REP observations, including energy spectra and flux directional information, during a period of approximately 2.5 years, from November 2015 to March 2018. We have identified 762 REP events during this period from which we obtain the distribution of radiation dose, relevant to extravehicular activities outside the ISS.